2018
DOI: 10.1016/j.ymgmr.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and rare deleterious variants in multiple genes suggest oligogenic inheritance in recurrent exertional rhabdomyolysis

Abstract: Exertional rhabdomyolysis is a metabolic event characterized by the release of muscle content into the circulation due to exercise-driven breakdown of skeletal muscle. Recurrent exertional rhabdomyolysis has been associated with metabolic myopathies and mitochondrial disorders, a clinically and genetically heterogeneous group of predominantly autosomal recessive, monogenic conditions. Although genetics factors are well recognized in recurrent rhabdomyolysis, the underlying causes and mechanisms of exercise-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
(43 reference statements)
1
18
0
Order By: Relevance
“…However, we found no RYR1 variants in 5 patients with ER with the 11 RYR1 variants found in 9 patients with EHI. We note that Sambuughin et al only found one RYR1 variant in seven patients with ER investigated by whole exome sequencing 38. Of the RYR1 variants found in patients with EHI, p.I3253T (found in patient #10) has been previously reported in combination with a nonsense RYR1 variant in trans in a patient with a congenital core myopathy39 and in a case of EHI from the French military 17.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, we found no RYR1 variants in 5 patients with ER with the 11 RYR1 variants found in 9 patients with EHI. We note that Sambuughin et al only found one RYR1 variant in seven patients with ER investigated by whole exome sequencing 38. Of the RYR1 variants found in patients with EHI, p.I3253T (found in patient #10) has been previously reported in combination with a nonsense RYR1 variant in trans in a patient with a congenital core myopathy39 and in a case of EHI from the French military 17.…”
Section: Discussionmentioning
confidence: 60%
“…The only variant we found in CACNA1S , p.R498H (annotated pathogenic by GAVIN), has not been reported in association with MH and was found in patient #52 with EHI who had a normal IVCT response. Interestingly, Sambuughin et al reported a variant affecting the same amino acid position ( CACNA1S p.R498L) in an individual with a history of EHI 38. CACNA1S , p.R498H and p.R498L have a combined MAF in low-risk populations of 0.00016 suggesting that the discovery of two variants at this amino acid position in a total of 71 patients with EHI/ER is unlikely to be due to chance.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Sambuughin et al about a genetic study of seven adult males with recurrent exercise-induced rhabdomyolysis [1]. The study raised the following comments.…”
mentioning
confidence: 99%
“…On the contrary, rhabdomyolysis is frequently a painless condition, manifesting with fatigue, exercise intolerance, and myoglobinuria.Too match, patient R465 did not complain about myalgia but about chest pain [1]. …”
mentioning
confidence: 99%
See 1 more Smart Citation